Deriving reversal in Old French nominal inflection - Crysmann, Berthold; Kihm, Alain (Proceedings of the 25th International Conference on Head-Driven Phrase Structure Grammar, 2018)
In this paper, we study Old French declension, a system which exhibitsthe theoretically challenging phenomenon of morphological reversal (Baerman,2007). Furthermore, the declension system of Old French only recognises asingle exponent -s, which marks different case/number combinations in differentparadigms, contrasting with the unmarked form. We show that reversal is onlyone of several syncretism patterns found in the language and propose that OldFrench declension is best understood in terms of two systematic syncretisms: anatural split between singular and plural for feminines, and a Paninian split formasculines that systematically marks the objective plural. Reversal, and otherseemingly morphomic splits arise as a result of idiosyncrasy in theNOM.SG cell, comprising inflection class-specific s-marking, as well as stem alternation andoverabundance. We provide a formal analysis in terms of Information-basedMorphology (Crysmann & Bonami, 2016) that effortlessly captures the systematic splits,as well as the variation in the nominative singular. We suggestthat the high degree of idiosyncrasy in this cell paired with the reduced frequency of overtnominative NPs when compared to objective NPs may serveto explain why the system was actually quite short-lived.